PENGARUH CELEBRITY ENDORSER DAN PROMOSI TERHADAP MINAT BELI SUSU CIMORY SQUEEZE - Andriani, Desika; Ansyah, Andri (Management Research and Business Journal, 2024)
This research aims to determine Celebrity Endorser's Interest in Buying Cimory Squeeze, Promotion methods for Interest in Buying Cimory Squeeze. what evaluation has been carried out on Cimory Squeeze's Purchase Interest, what obstacles were found by Celebrity Endorsers during the Promotion towards the Purchase Interest of Cimory Squeeze consumers. Data by conducting field surveys that are related to the problem being studied. This type of research was carried out to obtain primary data, consisting of: Observation, where data collection was carried out by reviewing Cimory Squeeze directly, to record information related to the problem to be studied, namely Celebrity Endorser and Promotion of Purchase Interest and interviews (interview) was conducted with questions and answers with the marketing and consumer departments of Cimory Squeeze. The results show that the Celebrity Endorser used in Cimory Squeeze using Tasyi Athasyia, has achieved good results in accordance with the company's own expectations, Influencers who can be trusted by their followers, have good skills to convince followers to buy the product being endorsed, Tasyi's appeal can make her followers always want to see Tasyi reviewing endorsements. The promotional methods used by Cimory Squeeze are, providing price cuts or discounts, using Influencer services, using print advertising, and using electronic advertising. Using this method can attract consumers to find out about Cimory Squeeze products. Evaluation carried out on interest in purchasing Cimory Squeeze, namely by carrying out promotions using banner print media, providing cashback, fostering exploratory interest in consumers and creating consumers' desire to recommend Cimory Squeeze products to friends, co-workers and family. Constraints on Celebrity Endorser, Promotion and Purchase Interest, namely: Constraints on Celebrity Endorser, difficulty in finding similar artists with characters that suit Cimory Squeeze products, selection based on good image, care about health, having influence to influence followers, and the existence of Artists who have allergies to yogurt. Constraints on Promotion, cimory is the first Yoghurt that can be eaten practically so it is quite difficult to introduce the product, there are rarely big events in malls to hold bazaars. Obstacles in buying interest, budget mismatch with the price of contracted artists and the difficulty of companies making Top of Mind products.